Stone formation in patients less than 20 years of age is associated with higher rates of stone recurrence: Results from the Registry for Stones of the Kidney and Ureter (ReSKU). Issue 3 (June 2020) - Li, Yi; Bayne, David; Wiener, Scott; Ahn, Justin; Stoller, Marshall; Chi, Thomas
Summary: Introduction: Nephrolithiasis is a major source of morbidity in the United States. In recent decades, there has been a notable increase in stone incidence in the pediatric population. We investigate whether recurrent stone formers who had their initial stone episode earlier in life are at risk for more frequent stone recurrences, compared to those with initial episodes later in life. We also examine possible risk factors that might change our approach to treatment of these patients. Methods: A review of prospectively collected data from the Registry for Stones of the Kidney and Ureter (ReSKU) from September 2015 to July 2018 was conducted to compare stone recurrence and other patient factors in patients who reported an initial stone episode prior to 20 years of age versus patients who reported an initial stone episode after age 20. Data on patient age, gender, BMI, family history, race, income, infectious symptoms, and number of prior stone episodes was analyzed. We excluded patients with a history of cystinuria stones. Univariate analysis was performed using Fisher's exact test and student's T test. Multivariate analysis was performed using logistic regression. Results: Of the 1140 patients enrolled during this study period, 472 patients were recurrent stone formers, and of these, 66 had their first stone episode prior to the age of 20. On univariate analysis, early stone formers were more likely to be female, present at a younger age, and have more prior stone episodes on enrollment. Using multivariate modelling to control for age, gender, race, BMI, family history, and number of stone episodes, early stone formers were more likely to be female (CI 1.17 – 3.54) and have more than one prior stone episode (CI 1.13 – 3.78). Late stone formers were more likely to have BMI > 30 (CI 0.26 – 0.94). Conclusion: Recurrent stone formers who have their first episodes prior to age 20 are more likely to present to stone clinics with multiple prior recurrences and hence more aggressive stone disease. Female gender seems to be a risk factor. Earlier stone formers should be encouraged to have close follow up and surveillance due to the increased rate of recurrence. Adult stone databases focusing on early presentations can improve understanding of pediatric stone disease. Summary Table Patient Variables Associated with Early Versus Late Stone Formation   Odds Ratio Confidence Interval (2.5–97.5%) Gender (Female) 2.03 1.17–3.54 Race (Non-caucasian) 0.83 0.46–1.47 BMI > 30 0.51 0.26–0.94 Family History of Nephrolithiasis 0.94 0.54–1.63 Infectious symptoms on Presentation 1.46 0.68–2.97 More than 1 prior stone episode 2.02 1.13–3.78 Patient variable associated with early stone formation. Multivariate analysis of associated patient factors comparing early vs late recurrent stone formers. Increased odds ratio indicates association with early stone former group. Statistically significant confidence intervals (p < 0.05) noted in bold .